THE IMPORTANCE OF STUDY ABOUT SEX AND GENDER IN HIGHER EDUCATION – ADDRESSING DISCRIMINATION TOWARDS LGBTQ YOUTH - Yasintha, Putu Nomy; Suwardani, Ni Putu (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Indonesia known as a democratic country, but there are still many cases of intolerance, one of which is a large-scale intolerance towards minorities such as LGBTQ people. Indonesia still considered as one of the homophobic countries due to religious norms and rules that limit the movement of LGBTQ people. Indonesian society still lives in a social life that upholds the value of heteronormativity in which heterosexuals are normal people and others considered as abnormal. LGBTQ discrimination also occurs to many adolescents, they do not have free space in society and are even unable to be who they really are even between family and closest friends. Education regarding gender and sexuality is necessary in Indonesian higher education institutions to be able to provide broader education to the community, especially adolescents, which in the end expected to increase public tolerance towards LGBTQ people. This study uses descriptive qualitative method by also distributing questionnaires anonymously at random to several informants. In addition, supporting data from various literatures used to support this research. The results showed that many LGBTQ adolescents felt marginalized by their family and friends. They have not been able to show their sexual orientation without being afraid to get judgement from the public.